Electron scattering emission in the light curves of stars with centrifugal magnetospheres. Issue 4 (4th February 2022) - Berry, I D; Owocki, S P; Shultz, M E; ud-Doula, A
ABSTRACT: Strongly magnetic, rapidly rotating B-type stars with relatively weak winds form centrifugal magnetospheres (CMs), as the stellar wind becomes magnetically confined above the Kepler co-rotation radius. Approximating the magnetic field as a dipole tilted by an angle β with respect to the rotation axis, the CM plasma is concentrated in clouds at and above the Kepler radius along the intersection of the rotational and magnetic equatorial planes. Stellar rotation can bring such clouds in front of the stellar disc, leading to absorption of the order of 0.1 mag (10 per cent of continuum flux). However, some stars with prominent CMs, such as σ Ori E, show an emission bump in addition to absorption dips, which has been so far unexplained. We show that emission can occur from electron scattering towards the observer when CM clouds are projected off the stellar limb. Using the rigidly rotating magnetosphere model, modified with a centrifugal breakout density scaling, we present a model grid of photometric light curves spanning parameter space in observer inclination angle i, magnetic obliquity angle β, critical rotation fraction W, and optical depth at the Kepler radius τK . We show that τK of order unity can produce emission bumps of the magnitude ∼0.05 seen in σ Ori E. We discuss the implications for modelling the light curves of CM stars, as well as future work for applying the radiative transfer model developed here to 3D magnetohydrodynamic simulations of CMs.